Estudo experimental da camada de água quente em um modelo em escalado Reator Multipropósito Brasileiro (RMB) - Gabriel Caio Queiroz Tomaz (2017)
The Brazilian Multipurpose Reactor (RMB) is a 30 MW open pool research reactor planned to be constructed in Brazil. Such type of reactor is built inside a deep pool of puried and demineralized water, providing radiological protection still keeping the core accessible for maintenance and refueling. However, dissolved ions become activated in the pool water due to the core neutron ux, releasing radiation in the reactor room when the activated elements reach the top. Thus high power open pool reactors, as RMB, have an auxiliary thermal-hydraulic circuit that creates a Hot Water Layer (HWL) on the pools top, keeping the activated water under the HWL and mitigating the dose rate to which the operators are exposed to. The Centro de Desenvolmento da Tecnologia Nuclear (CDTN) built a 1/10 scale experimental bench of the RMBs pool for the HWL investigation. This work presents the results of the pools heating due to the reactor startup in the HWL stability.